PENGARUH PEMBERIAN PUPUK KASCING DAN PEMOTONGAN UMBI TERHADAP PERTUMBUHAN DAM PRODUKSI BAWANG MERAH (Allium ascalonicum L.) - Eniwati Harianja; Syamsul Bahri; Boy Riza Juanda (Jurnal Cakrawala Ilmiah, 2024)
This study aims to determine the effect of vermicompost fertilizer and tuber cutting and the interaction of the two treatments on growth and production on the growth and production of shallots (Allium ascalonicum L.)". The research has been carried out in Sidorejo Village, Langsa Lama District, Langsa City, from October to December 2022. This study used a factorial pattern Group Randomized Design (RAK) consisting of 2 factors, namely vermicompost fertilizer (K) which consisted of 4 levels, namely: K 0: Control, K 1 : 2 kg / plot, K 2 : 4.1 kg / plot, K4 : 6.1 kg / plot. The cutting factor of tubers (U) consists of 3 levels, namely, U0 : No Cutting, U 1 : Cutting 1/4, U2 : Cutting 1/3. The parameters observed in this study include: plant height (cm) and number of leaves (strands) aged 15, 30 and 45 HST, number of tubers per sample (cloves), weight of fresh plant tubers per sample and per plot (g), weight of dried plant tubers per sample and per plot (g) at the age of 60 HST